Nexus of social work services and disaster management services : an afrocentric perspective - Matlakala, Frans Koketso (My University, 2021)
Refer to the document
Thesis (Ph. D. (Social Work)) -- University of Limpopo, 2021
Keywords: Natural disasters; Social work; Indigenous knowledge systems; Climate change; Rural areas; Social service -- South Africa -- Limpopo; Natural disasters -- South Africa -- Limpopo; Disaster relief -- South Africa -- Limpopo